Implementation Of Road Maintenance Policy At The Indramayu Public Works And Spatial Planning Office (PUPR) - Tiara Selamonika; Nuraini Putri Febriani; Sri Wulandari; Moh. Sutarjo; Hamzah Restu Lesmana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study examines the implementation of road maintenance policies by the Public Works and Spatial Planning Office (PUPR) of Indramayu Regency. Good road infrastructure is very important to support people's daily activities and economic growth. This study uses a qualitative approach with the policy implementation theory from Tachjan (2006) which includes the role of actors and organizations, interaction and communication, context and environment, resources and constraints, and evaluation and learning. The results of the study show that the implementation of road maintenance policies in Indramayu still faces several obstacles, namely limited financial and human resources, as well as inhibiting factors such as 1) resources that are still inadequate both for tools, facilities, time or human manpower 2) information and communication that does not run in both directions between the PUPR Office and the community 3) the division of potential such as unclear organizational and bureaucratic structures causing the policy program to seem to float without knowing who is in control.